An Evaluation of Graduates’ Employment of Courses and Vocational Training Institutions - Suseno, Imam (LPPM Undiksha, 2023)
Evaluation of graduates’ employment of Courses and Vocational Training Institutions (LKP) is very important to conduct, as a step to obtain feedback on programs or policies that have been implemented by vocational LKP in Indonesia. However, the absorption data for vocational LKP graduates has not been properly recorded at the present. Therefore the aims of this study is to analyze achievement of performance targets at the Directorate of Courses and Training (Dit-Suslat), Ministry of Education and Culture. This study using the Goal-Oriented Evaluation of program evaluation model from Ralp W Tyler. The results of the analysis point out that the target percentage of courses and trainings graduates in one year who get a job or become an entrepreneur has not reached the set target. Most LKP graduates are absorbed in the trading sector, manufacturing industry, as well as health services & social activities. Future needed labor are massively from the sectors of healthcare, construction, manufacturing and retail. Clerical, routine and repetitive jobs start to be replaced by robots and intelligent machines. The implementation of vocational LKP must be transformed in carrying out link and match as a whole.